The clean energy ministerial: motivation for and policy consequences of membership - Tosun, Jale; Rinscheid, Adrian (International political science review, 2020)
What motivated national governments to join the Clean Energy Ministerial (CEM), a climate club founded in 2010? And to what extent have the club members participated in policy initiatives developed by the CEM? Our analysis shows that combinations of (a) the expected benefits of club membership and (b) the leadership of the USA induced the governments of Australia, Brazil, Canada, China and the United Arab Emirates (UAE) to join the CEM. The importance of these two factors varied across countries. Participation levels in the CEM’s policy initiatives varied over time. While this variation happened in a ‘proportionate’ manner for Australia, Canada and China, we observed singular instances of ‘disproportionate’ changes in levels of policy effort for the UAE and Brazil. Overall, our findings suggest that climate clubs constrain the behaviour of its members by discouraging them from engaging in sustained policy under-reactions.
Gesehen am 25.02.2021